Front Cover. Issue 1 (13th December 2018) - Meester, J.A.N.; Verstraeten, A.; Alaerts, M.; Schepers, D.; Van Laer, L.; Loeys, B.L.
Abstract : The cover image is based on the Review Overlapping but distinct roles for NOTCH receptors in human cardiovascular disease, by J.A.N. Meester et al., https://doi.org/10.1111/cge.13382 . Abstract : The cover image is based on the Review Overlapping but distinct roles for NOTCH receptors in human cardiovascular disease, by J.A.N. Meester et al., https://doi.org/10.1111/cge.13382 .